ANALISIS KONTEN HIGH ORDER THINKING SKILLS (HOTS) SOAL FISIKA SBMPTN TAHUN 2018 - Amalia, Rizki Firda; Wahyuni, Siti (UPEJ Unnes Physics Education Journal, 2020)
All types of selection test for state universities are accompanied by intense competition levels. SBMPTN is one of this test that provides the highest quota of prospective students. Some questions tested require high order thinking skills while students are accustomed to work on low order thinking skills on their high school. The challenge for students is the students have to know the type of questions tested in SBMPTN and accustomed to work the kind of questions. This study aimed to find out the cognitive level classification in SBMPTN physics problems based on revised Bloom?s taxonomy and characteristics of SBMPTN physics problems based on indicator of critical thinking skill and problem solving skills. This study was qualitative research using SBMPTN physics problems code 402 in 2018, as its subject. The result of this study showed that in 2018 there were 73.33% SBMPTN physics questions included HOTS categories.  In addition, it obtained that in 2018, SBMPTN physics problems contained critical thinking skills of 80%. Furthermore, the availability of problem solving skill?s indicators in the SBMPTN physics question was found to be 60%.